Assessment with indentation techniques of the local mechanical behavior of joints in polymer parts - Lach, R; Hutař, P; Veselý, P; Nezbedová, E; Knésl, Z; Koch, T; Bierögel, C; Grellmann, W (Polimery, 2013)
The paper summarizes our investigations performed with micro- and nanoindentation techniques and results presented in literature, concerning local mechanical behavior of welded joints [polyamide 6, polypropylene, polyethylene (high density and crosslinked polyethylene), poly(vinyl chloride)] and weld lines (polypropylene, polycarbonate, polystyrene) of amorphous and semicrystalline polymers. For amorphous polymers, minimum of hardness and indentation modulus in the joint are found or no change in the properties were stated, whereas for semicrystalline polymers, hardness and indentation modulus mostly pass through a maximum in the weld line, the welded joint or the heat-affected zones.